Pulmonary hypertension is associated with systemic arterial hypertension among patients with normal diastolic function. (14th October 2021) - Itelman, E; Segal, M; Kuperstein, R; Feinberg, M; Segev, A; Segal, G; Maor, E; Grossman, E
Abstract: Introduction: The association of pulmonary and systemic arterial hypertension is believed to be mediated through hypertensive left heart disease. The purpose of the current study was to investigate whether pulmonary arterial hypertension (PAH) is associated with systemic arterial hypertension among patients with apparently normal left heart diastolic function. Methods: Consecutive patients who had echocardiographic evaluation between 2007 and 2019. Patients with disease states that are known to be associated with PAH including diastolic dysfunction were excluded from the analysis. Estimated right ventricular systolic pressure (RVSP) was extracted for all patients from the echocardiographic reports. PAH was defined as estimated RVSP >40 mmHg. Multivariate logistic regression models were applied. Results: Final study population included 25, 916 patients with a median age of 59 (IQR 44–69), of whom 12, 501 (48%) were male and 13, 265 (51%) had systemic arterial hypertension. Compared with normotensive patients, hypertensive patients were 3.2 times more likely to have PAH (95% CI; 2.91–3.53, p<0.001). A multivariate model adjusted for clinical and echocardiographic parameters that are known to be associated with PAH demonstrated that hypertensive patients are almost 3 times more likely to have PAH (95% CI 2.45–3.15, p<0.001). The association was significant in multiple subgroups but was more significant among women compared with men (OR 3.1 vs. 2.4, p for interaction <0.001). Conclusions: PAH is associated with systemic arterial hypertension irrespective of left heart disease. The association is more pronounced among women. FUNDunding Acknowledgement: Type of funding sources: None.